TEKS KABA SABAI NAN ALUIH DAN NASKAH TEATER “SIKLUS DENDAM SABAI” (Tinjauan Resepsi Sastra) - Yuli Sartika (Jurnal Elektronik WACANA ETNIK, 2011)
Through active reaction, readers give response in new form of works. “Siklus Dendam Sabai” is one of this new form of kaba Sabai Nan Aluih. This article describes the reader response which brings differences between those two objects. Furthermore, the differences (theme and plot) are manifest of active reader background which shows in the new form of the work.